Analisis Respon Guru dan Mahasiswa Terhadap Teknologi di Era Globalisasi - Eka Susanti; Lia Rismawati; Zaki Aimansyah (CV. Ulil Albab Corp, 2023)
This research aims to determine the influence of technology on student and teacher responses. This type of research is non-experimental quantitative research with descriptive quantitative research methods. The sample for this research was 30 teachers in 10 elementary schools in Percut Sei Tuan District using non probability sampling techniques with saturated samples. Data collection used several instruments, namely questionnaires and observation sheets on the use of technology and teacher response questionnaires. Data analysis uses a simple linear regression test and t-test to see how much influence the independent variable has on the dependent variable. The results of the research show that the results of the simple linear regression test and the significance test showed that the contribution contributed by variable X to variable Y was Y = 22.22 +0. 604X with a value of r = 0.542. The results of the analysis using the significant test tcount (3.127) > ttable (2.342), then Ho is rejected, thus meaning that there is a significant influence between the use of social studies teaching aids on teacher performance